2021
DOI: 10.1177/08971900211010680
|View full text |Cite
|
Sign up to set email alerts
|

Acute Diuretic-Sparing Effects of Sacubitril-Valsartan: Staying in the Loop

Abstract: Background: Previous literature has suggested a potential diuretic sparing effect as early as 6 months following sacubitril-valsartan initiation in patients with heart failure with reduced ejection fraction (HFrEF); however, whether this effect manifests earlier after initiation is unclear. Objective: To evaluate the acute diuretic-sparing effects of sacubitril-valsartan. Methods: This was a single-center, retrospective analysis of outpatients with HFrEF initiated on sacubitril-valsartan with follow up within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The study was also limited by a small sample size of 120 patients. 6 Our study included more than 400 patients and showed that there were no significant differences in the dose of loop diuretic during 6-month follow-up period following the initiation of sacubitril/valsartan therapy. The diuretic effects of sacubitril/valsartan may not be clinically significant during 6-month follow-up period.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The study was also limited by a small sample size of 120 patients. 6 Our study included more than 400 patients and showed that there were no significant differences in the dose of loop diuretic during 6-month follow-up period following the initiation of sacubitril/valsartan therapy. The diuretic effects of sacubitril/valsartan may not be clinically significant during 6-month follow-up period.…”
Section: Discussionmentioning
confidence: 77%
“…Sacubitril is a neprilysin inhibitor which allows for increased expression of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP). 6 Wang et al compared the effects of sacubitril/valsartan to the effects of valsartan alone, on natriuresis, diuresis, and serum potassium levels in Asian patients with salt-sensitive hypertension. 7 They found that the first dose of sacubitril/ valsartan significantly increased 6-and 24-hour natriuresis and diuresis compared to the first dose of valsartan only.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations